Establishing the Interaction between Training Methods and Power Levels in Wrestling: A 2x3 Factorial Design of Hip Toss Skills - Juhanis, Juhanis; Badaru, Benny; Bausad, Andi Anshari (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to evaluate the effects of resistance band exercises, good morning drills, and bicep curls on improving the hip throw technique among wrestling athletes, considering their initial power levels. Materials and methods. This study employed a 2x3 factorial design involving 66 male students, grouped based on power levels (high and low) and training methods. The training was conducted over six weeks with a frequency of three weekly sessions. The measured parameters included improvements in hip throw technique skills, encompassing strength, stability, and execution speed. Data analysis was performed using ANOVA and Tukey’s test to evaluate significant differences between groups. Results. The results indicated a significant main effect of the training method factor (A) on hip toss skills (F = 5.413, p = 0.007), demonstrating that variations in training methods led to marked differences in skill outcomes. The second main effect, power level (B), showed an even more substantial influence (F = 99.426, p = 0.000), indicating that athletes’baseline power plays a crucial role in determining hip toss performance. Regarding the interaction effect, there was a considerable interaction between training methods and power levels (F = 7.914, p = 0.001). Conclusions. This study concludes that resistance band exercises are the most effective method for athletes with high power in enhancing dynamic strength and flexibility relevant to hip toss techniques. The “good morning” exercise effectively supports postural stability, while bicep curls contribute to grip strength. A multidimensional approach integrating resistance band exercises, good morning drills, and bicep curls provides complementary benefits for improving hip toss technique skills in wrestling. These findings can serve as a foundation for coaches to design evidence-based training programs tailored to the specific needs of athletes.